THE IMPLEMENTATION OF CARD SORT STRATEGY IN INCREASING STUDENTS’ ABILITY TO USE ADVERB IN SENTENCE AT MTs MUHAMMADIYAH KISARAN - Khairun Niswa (English Teaching and Linguistics Journal (ETLiJ), 2021)
This study was conducted to find out the implementation of Card Sort strategy in increasing students’ ability to use Adverb in Sentence. The population of this study was the grade VIII students of MTs Muhammadiyah 2019/ 2020 academic years. The writer used cluster random sampling, there were 32 students as the samples And this research applied by classroom action research. The technique of analyzing data of this study was applied by using qualitative and quantitative data. The qualitative data were taken from interview, observation sheet, and document. The quantitative data were taken from the test. The result of the analysis showed that the mean of the first cycle was 59.37. The mean of second cycle was 78.12. The percentage of students who got point up to 65 also grew up. In the pre-test, there was only 15.62% (five students) who got point 65 above. In the post test of cycle I, there was 59.37% (nineteen students) who got point 65 above. It means that there was improvement about 43.75%. In the post test of cycle II, there was 78.12% (twenty one students) who got points 65 above. The improvement was about 18.75%. The total improvement of the students’ score from the pre-test to the post test of cycle II was 62.5%. It indicated that the implementation of Card Sort strategy was effective as it could increase students’ ability to use Adverb in Sentence